PERANCANGAN PUSAT PERBELANJAAN TENGGARONG DENGAN PENDEKATAN ARSITEKTUR REGIONALISME - Efendy, Zulfikhar Achmad; Prasetyo, Prasetyo; Mudrajad, Dimas Bintang (LPPM Universitas 17 Agustus 1945 Samarinda, 2021)
A shopping center is a group of commercial buildings built and erected at a planned location,developed, started and organized into an operating unit, related to the location, size, type of shopand shopping area of the unit. The design of a shopping center is something that is underconstruction, so that various cities want to plan a shopping center that can serve as supportingfacilities. Therefore, the existence of shopping centers has a positive impact on the development ofa city. So a shopping center in Tenggarong is needed with supporting facilities, and uses aregionalism architectural approach that displays the cultural characteristics of the Tenggarongpeople. The method used to achieve the goals and objectives consists of the data collection stage,the analysis stage and the building design concept stage. The results of the discussion on theresearch on the design of the Tenggarong shopping center with an architectural regionalismapproach as an element to introduce the cultural characteristics that exist in Tenggarong. Like theulapdoyo woven cloth, the Erau tradition and the mythological animals that exist in the Tenggarong area, which are emphasized on the form of the building's facade. In the analysis of the amount ofspace, it has a total area of 78,641.91 m² with KDB 14,468 m² and KDH 21,702 m², which isdivided into 6 floors and has 315 shops from 1 building period. transformation of the shape of thebuilding using a combined Dayak shield form. And the building formation adopted from the Kedatonbuilding in the 1900s. So that it can become a new icon in Tenggarong.Keywords: Design, Tenggarong, Regionalism